THE ENGLISH AS FOREIGN LANGUAGE (EFL) STUDENTS’ PERSPECTIVES ON THE READING EDUCATIONAL COMICS BASED ON LOCAL WISDOM “THE STORY OF CANDI PARI - Nadliyah Putri Syalwa; Vidya Mandarani; Yuli Astutik (Premise: Journal of English Education and Applied Linguistics, 2026)
This qualitative study explores seventh-grade students' perspectives on using "The Story of Candi Pari" educational comic in English reading instruction at SMP Dharma Wanita 7 Tanggulangin, East Java. Data was collected through semi-structured interviews with 10 selected students, alongside observations and documentation, which were later analyzed through thematic analysis. Eight themes emerged in response to two research questions. Students identified four strategies that enhanced reading skills: the integration of visual and textual components aided comprehension; gaining vocabulary in context was facilitated by various hints; making comics led to increased engagement; and visual panels helped in grasping narrative structure. Four additional themes represented the students' views: increased enthusiasm and enjoyment, a preference for visual formats that reduce reading anxiety, cultural significance which contributes to a deeper understanding through familiar local material, and pride in their local identity and history. The results indicate that educational comics rooted in local narratives can serve effectively as both instructional and reading resources. They encompass multiple dimensions of reading development, such as cognitive, metacognitive, motivational, and sociocultural elements. This offers substantial proof of the effectiveness of culturally relevant multimodal approaches in secondary education in Indonesia.